Adaptability of Growth and Yield on 5 varieties of Shallot (Allium ascalonicum L) in Wet Highland - Agustina E Marpaung; Rini Rosliani (Journal of Tropical Horticulture, 2019)
In general, shallot was planted in low land to highland, but it usually planted in area has rain fall and humidity not high, because can effect to the yielding, so that needed the adaptive varieties in the condition. The aim of the research was to determine the growth and yield of some varieties of shallot adaptive in wet highlands. The research conducted in Berastagi experimental farm, Dolat Rayat district, Karo regency, with type of the soil is andisol and altitude of 1,340 m asl. The research was beginning from September - December 2015. The design was used randomize block non factorial with 5 replication. The treatment was shallot varieties (Bima, Maja, Trisula, Agrihorti 1 and Agrihorti 2). The shallot seeds were from Java. The result showed that the Agrihorti 1 and Bima varieties had a more adaptive vegetative growth in wet highland than 3 other varieties. Agrihorti 1 and Bima varieties produced the highest bulb production respectivaly i.e.12,76 kg / 5 m2 and 12,61 kg / 5 m2. Agrihorti 1 varieties have the largest bulb diameter 2,99 cm. Shallot Agrihorti 1 varieties adaptive in the wet highland.